Shakespeare the complete works of William Shakespeare. - Shakespeare, William 1564-1616 (Creative Multimedia Corporation, 1992)
American and Queen's English versions of the works of Shakespeare including full text of plays, poems, and sonnets. Features full text index, index browsing, and table of contents.